Histopathology of Placentae in Pre-Eclampsia: A Review - C Krishnaveni (Journal of Clinical and Biomedical Sciences)
Preeclampsia (PE) is a pregnancy related complex multisystemic disorder with a triad of symptoms including increased blood pressure, oedema, and proteinuria phenotypically observed after 20 weeks of gestation. The disorder worsens amongst the early onset patients PE (< 34 weeks). The placenta shares more responsibility for the cause of PE. The placenta is an essential organ for pregnancy and assists in the development of the fetus. It shares the same stress and strain to which the fetus is exposed. Any disease which affects the mother has a great impact on the placenta and also placenta acts as a future evidence of mother and fetus health. Therefore careful observation of histopathological changes can provide clinically useful information to pave the way for pathophysiology of PE. So the histopathological parameters like distal villous hypoplasia, accelerated villous maturity, increase in syncytial knots, immature villi, chorangiosis, fibrin deposition, infarction, and calcification are evident in histopathological observations of PE placentae. Keywords: Histopathology of placenta, Pre-eclampsia, Distal Villous Hypoplasia, Chorionic Villi, Villous maturity.